The measurement of maintenance function efficiency through financial kpis (2014)
The measurement of the performance in the maintenance function has produced large sets of indicators that due to their nature and disparity in criteria and objectives have been grouped in different subsets lately, emphasizing the set of financial indicators. To generate these indicators properly is necessary to have accurate input data. Hence in this paper we propose a comprehensive model of consensus between the different stakeholders involved in the maintenance function. This will bring about the accurate determination of the maintenance costs of an organization.